Pengaruh Pengetahuan Kewirausahaan Terhadap Perilaku Berwirausaha Siswa - Adinda Pratiwi; Sandi Sandi; Hamka Hamka (Journal on Education, 2025)
This study aims to determine how the correlation of teacher teaching variations on student learning motivation. The type of research used is quantitative research method. The data obtained and processed are the results of questionnaire answers from students of class XI OTKP SMK Negeri 4 Bone. The data collection techniques used in this research are observation, documentation and questionnaires by going directly to the research location. Based on the test results that have been done, partially shows that the variable knowledge of entrepreneurship (X) has a significant effect on entrepreneurial behavior (Y) class XI OTKP SMK Negeri 4 Bone. This means that the first hypothesis (Ha) is accepted, because the value of tcount> ttable or 11.089> 1.697 sig value of 0.000 <0.05. Thus Ha is accepted. Strong knowledge of entrepreneurship can help students identify new opportunities in an ever-changing market which in this case shows an entrepreneurial attitude. Students can learn to identify market needs and develop innovative products or services to meet those needs. Thus, an understanding of entrepreneurship not only affects individual student behavior, but can also have a positive impact on economic growth.